Cerebral Venous Sinus Thrombosis Following COVID-19 Vaccination: A Systematic Review. (February 2022) - Jaiswal, Vikash; Nepal, Gaurav; Dijamco, Patricia; Ishak, Angela; Dagar, Mehak; Sarfraz, Zouina; Shama, Nishat; Sarfraz, Azza; Lnu, Kriti; Mitra, Saloni; Agarwala, Preeti; Naz, Sidra; et al.
Introduction: COVID-19 vaccines became available after being carefully monitored in clinical trials with safety and efficacy on the human body. However, a few recipients developed unusual side effects, including cerebral venous sinus thrombosis (CVST). We aim to systematically review the baseline features, clinical characteristics, treatment, and outcomes in patients developing CVST post-COVID-19 vaccination. Methods: This study was conducted according to the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) 2020 guideline. Investigators independently searched PubMed, Embase, and Google Scholar for English language articles published from inception up until September 10, 2021, reporting the incidence of CVST post-COVID-19 vaccines. We analyzed CVST patients' baseline data, type of vaccines, clinical findings, treatment, and outcomes. Our systematic review process yielded patient-level data. Result: The final analysis included 25 studies that identified 80 patients who developed CVST after the COVID-19 vaccination. Of the 80 CVST cases, 31 (39.24%) patients died. There was no significant relationship between mortality and age ( P  = .733), sex ( P  = .095), vaccine type ( P  = .798), platelet count ( P  = .93), and comorbidities such as hypertension ( P  = .734) and diabetes mellitus ( P  = .758). However, mortality was associated with the duration of onset of CVST symptoms after vaccination ( P  = .022). Patients with CVST post-COVID-19 vaccination were more likely to survive if treated with an anticoagulant ( P  = .039). Patients who developed intracranial hemorrhage ( P  = .012) or thrombosis in the cortical vein ( P  = .021) were more likely to die. Conclusion: COVID-19 vaccine-associated CVST is associated with high mortality rate. Timely diagnosis and management can be lifesaving for patients.